2020
DOI: 10.3390/insects11080484
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Dimorphism in the Multielemental Stoichiometric Phenotypes and Stoichiometric Niches of Spiders

Abstract: Nutritional limitations may shape populations and communities of organisms. This phenomenon is often studied by treating populations and communities as pools of homogenous individuals with average nutritional optima and experiencing average constraints and trade-offs that influence their fitness in a standardized way. However, populations and communities consist of individuals belonging to different sexes, each with specific nutritional demands and limitations. Taking this into account, we used the ecological … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…It has also been hypothesized that O. bicornis females collect pollen species in proportions that re ect the sex-speci c nutritional needs of their daughters and sons 10,42 . Sex-speci c differences in stoichiometric phenotypes that can be re ected in stoichiometric niches have also been detected in other invertebrates, including amphipods and spiders 31,43 . Our preliminary experiment showed that the scarcity of speci c nutrients in a larval diet indeed impacted bee development in a sex-dependent manner 18 , as predicted by theoretical calculations based on stoichiometric phenotypes and stoichiometric mismatches between consumers and their food 10 .…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…It has also been hypothesized that O. bicornis females collect pollen species in proportions that re ect the sex-speci c nutritional needs of their daughters and sons 10,42 . Sex-speci c differences in stoichiometric phenotypes that can be re ected in stoichiometric niches have also been detected in other invertebrates, including amphipods and spiders 31,43 . Our preliminary experiment showed that the scarcity of speci c nutrients in a larval diet indeed impacted bee development in a sex-dependent manner 18 , as predicted by theoretical calculations based on stoichiometric phenotypes and stoichiometric mismatches between consumers and their food 10 .…”
Section: Discussionmentioning
confidence: 91%
“…The demand for resources for growth and development, as re ected in organismal stoichiometry, is usually studied by comparing different species, but research has also started to focus on individual variations in the chemical compositions of bodies; much of this variation is expected to be attributable to sex differences 19,31,32 . This is expected because processes involved in life history evolution and population dynamics are likely to differentially affect females and males, thus imposing sex-speci c nutritional limitations 27,32 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations